Identification of biological characteristics and prelimilary research on genetic transformation of the filamentous fungus Penicillium chrysogenum originated from Vietnam - Xuan Tao, Vu; Van Tuan, Tran (VNU Journal of Science: Natural Sciences and Technology, 2017)
Penicillium chrysogenum is a well-known filamentous fungus for production of penicillin and some valuable secondary metabolites. In this study, we indicated that two strains VTCC-F1170 and VTCC-F1172 identified as P. chrysogenum , which are preserved at Vietnam Type Culture Collection (VTCC) of Vietnam National University Hanoi, exhibited the ability of antibiotic production to inhibit the tested bacterium Staphylococcus aureus on the agar plates by diffusion assays. Additional analyses of the morphological characteristics and the rDNA ITS (internal transcribed spacer) sequence confirmed that the identification of both strains as P. chrysogenum was completely accurate. These important evidences guaranteed that the fungal strains are reliable for the researches on genetic engineering of P. chrysogenum . Experimental assays of antibiotic susceptibility showed that the growth of both strains VTCC-F1170 and VTCC-F1172 was completely inhibited by nourseothricin at 50 μg/ml and phleomycin at 150 μg/ml. Using the Agrobacterium tumefaciens -mediated transformation method, we have succesfully transferred the nourseothricin resistance marker into the genome of the VTCC-F1170 strain.